Liver ultrasound elastography for the evaluation of periportal fibrosis in schistosomiasis mansoni: A cross-sectional study. - Joelma Carvalho Santos; Andrea Dória Batista; Carla Maria Mola Vasconcelos; Roberto Souza Lemos; Valter Romão de Souza Junior; Alain Dessein; Hélia Dessein; Silvia Maria Lucena Montenegro; Edmundo Pessoa Almeida Lopes; Ana Lúcia Coutinho Domingues (Public Library of Science (PLoS), 2018)
Background ARFI elastrography has been used as a noninvasive method to assess the severity of liver fibrosis in viral hepatitis, although with few studies in schistosomiasis mansoni. We aimed to evaluate the performance of point shear wave elastography (pSWE) for predicting significant periportal fibrosis (PPF) in schistosomotic patients and to determine its best cutoff point. Methodology/principal findings This cross-sectional study included 358 adult schistosomotic patients subjected to US and pSWE on the right lobe. Two hundred two patients (62.0%) were women, with a median age of 54 (ranging 18-92) years. The pSWE measurements were compared to the US patterns of PPF, as gold standard, according to the Niamey classification. The performance of pSWE was calculated as the area under the ROC curve (AUC). Patients were further classified into two groups: 86 patients with mild PPF and 272 patients with significant PPF. The median pSWE of the significant fibrosis group was higher (1.40 m/s) than that of mild fibrosis group (1.14 m/s, p<0.001). AUC was 0.719 with ≤1.11 m/s as the best cutoff value for excluding significant PPF. Sensitivity and negative predictive values were 80.5% and 40.5%, respectively. Whereas, for confirming significant PPF, the best cutoff value was >1.39 m/s, with specificity of 86.1% and positive predictive value of 92.0%. Conclusions/significance pSWE was able to differentiate significant from mild PPF, with better performance to predict significant PPF.